Raymond Pierre Paul Westerling: Upaya Mendirikan Negara Indonesia Timur 1946-1947 - Kurniawan, Putut Wisnu; F, Aurora Nandia; Wibowo, Wayan Dion (Universitas Batanghari Jambi, 2024)
Japan's defeat in World War II made Indonesia an independent country, but the Dutch did not recognize Indonesia's independence and tried to return to power by conducting negotiations and military operations. This research aims to describe and analyze the efforts made by Westerling to establish the State of Eastern Indonesia and the impact resulting from the establishment of NIT. The results of this research are that the State of East Indonesia was formed as an attempt by the Dutch to return to power in Indonesia because the Dutch still considered Indonesia as a colony after the Second World War ended. Westerling's efforts to help or accelerate the establishment of the State of East Indonesia were by capturing and executed republicans who opposed the establishment of the State of East Indonesia and carried out cleansing in South Sulawesi to prevent the area from joining Indonesia. The impact of the founding of the State of Eastern Indonesia was that the form of the Indonesian state became federal, the economy in the areas where the cleanup was carried out became dead and chaotic, the social conditions of the people in the cleanup areas became disturbed and the people became traumatized by the sound of cars and politics in Indonesia became unstable due to changes in the shape of the state